(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Introduction: Prolonged patient waiting time in healthcare facilities is a significant factor influencing healthcare service utilization and patient satisfaction. It impacts both the quality of care and patient trust in the healthcare system. In Nigeria, particularly at Adeoyo Maternity Teaching Hospital, excessive waiting times have become a persistent issue, primarily due to overcrowding, staff shortages, and inadequate infrastructure. Objectives: This study aims to investigate the impact of prolonged waiting times on healthcare service utilization and patient satisfaction at Adeoyo Maternity Teaching Hospital. Specifically, it seeks to identify factors contributing to delays and assess how waiting times affect patient satisfaction and service utilization. Method of Analysis: A descriptive survey design was employed, using a structured questionnaire to collect data from 200 patients attending four outpatient clinics: General Outpatient Department (GOPD), Antenatal Care (ANC), Family Planning, and Antenatal Outpatient Department (AOPD). Data were analyzed using SPSS version 20.0, with descriptive statistics and chi-square analysis used to examine the relationships between waiting times and patient satisfaction. Results: The study found that significant delays were caused by factors such as late arrival of doctors (60%), patient overcrowding (65%), and inefficiencies in administrative processes, particularly at billing points (70%). A substantial proportion of patients (41%) reported waiting over 40 minutes to see a doctor, which contributed to dissatisfaction with services. Administrative delays, including misplaced medical records, further exacerbated waiting times. Despite these issues, 52% of patients expressed overall satisfaction with the services, although they still experienced frustration due to prolonged waiting times. Conclusion: The study concludes that addressing staffing shortages, optimizing scheduling systems, and improving administrative processes can significantly reduce waiting times and enhance patient satisfaction. Introducing digital solutions, such as electronic health records and mobile applications for appointment scheduling, could streamline operations and reduce delays. Improving the punctuality of healthcare providers and fostering a patient-centered approach are also critical steps in enhancing the patient experience at Adeoyo Maternity Teaching Hospital.